ANALISIS PENGARUH MOBILE BANKING TERHADAP KEPUASAN DAN LOYALITAS NASABAH BANK MANDIRI CABANG JAKARTA - Markonah Markonah (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2019)
The purpose this research is to analysis the influence Mobile Banking toward Customer Satisfaction And Loyalty Bank Mandiri, Jakarta. The Adult, Banking competing to provide additional services so that its customers feel satisfied, among other things is a banking transaction services. Banking transaction services through mobile banking (mobile) with using the Network data telecoms That can be easy to used by Customer to review Transactions check balance, check mutations transactions, transfer between accounts, transferring real time, Pay Bills, Purchase reload mobile and other Transaction, Banking businesses include the Three Main activities are: Raise funds, funds flow, and provide other banking services. While Satisfaction is feeling happy or disappointed someone who emerged after comparing the performance (yield) of products thought to the performance (or outcome) is expected. Loyalty is a customer loyal in buying a particular brand of products with a high intensity. This research method, the data used is primary data used population are customers of PT Bank Mandiri (Persero) Tbk. Branch Jakarta Industrial Pulogadung at Jl. Pulobuaran No. 2 Pulogadung Region of Industrial Jakarta, amounting to 300,000 people, sampling approach used is purposive sampling, with Slovin formula n = N / (1 + N.e2) obtained a sample of 100 respondents, but because of data collection by using a questionnaire, distributed to 400 respondents returned 365 respondents, but who use mobile banking only 50 respondents. Results obtained by using á = 5%, 95% degree of confidence is as follows:1. Significance of 0,040 which means 0.05 so: Services (mobile banking) positive effect on customer satisfaction Bank Mandiri2. Significance of 0,031, which means 0.05 so: Services (mobile banking) positive effect on customer loyalty Bank Mandiri.3. The significance of 0.035 which means 0.05 so: Customer satisfaction positively affects customer loyalty bank Mandiri.So that it can be concluded that the better the service, the more satisfied customers, and customer satisfaction is increased it will increase the level of customer loyalty. And the better the service will increase the customer loyalty. The suggestions for further research is that research carried out in more detail which is part of mobile banking, such as SMS banking, and so on.